Association of Time-Lines of COVID-19 Seropositivity with Antibody Ratio Levels - Mushtaq, Saadiya; Din, Nasir Ud; Shah, Abid Hussain; Riaz, Omair; Azam, Khalid; Khan, Sara Waqar (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the persistence of IgG antibodies against SARS-CoV-2 and the association of timelines of COVID-19 seropositivity with antibody ratio levels. Study Design: Cross-sectional study. Place and Duration of Study: Combined Military Hospital, Lahore, from Apr to Sep 2020. Methodology: The serum of 250 patients recovered from COVID-19 was collected to detect anti-SARS-COV-2 IgG antibodies. Anti-SARS Cov-2 IgG was measured by Semi-Quantitative Enzyme-Linked Immuno-Sorbent Assay (ELISAs), and the association of timelines of COVID-19 seropositivity with antibody ratio levels was determined. Results: Out of 250 study participants, males were 220 (88%) while females were 30 (12%), mean age being 35.25 years ± 9.096 years. In the timeline of 31-60 days after the first positive COVID-19 PCR, 27 out of 44 (61%) were seropositive. In the 61-90 days’ timeline, 79 out of 155 (51%) were seropositive, in the timeline of 91-120 days after the first positive PCR, 52 out of 76 (68%) were seropositive, and in the timeline of 121-150 days, 12 out of 15 (80%) of the study participants were seropositive for COVID-19. Conclusion: Serological IgG immune response against SARS-CoV-2 persists up to five months after active COVID-19 infection in most individuals in the Pakistani population.